2022
DOI: 10.1158/1055-9965.epi-22-0868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Variants in the Nicotine Metabolism Pathway on Nicotine Metabolite Levels in Smokers

Abstract: Background: Nicotine metabolism is a major factor in nicotine dependence, with approximately 70-80% of nicotine metabolized to cotinine in Caucasians. Cotinine formation is catalyzed primarily by CYP2A6, which also converts cotinine to trans-3’-hydroxycotinine (3HC). The goal of the present study was to examine the effects of CYP2A6 deficiency on nicotine metabolism profiles in vivo and the importance of genetic variants in nicotine metabolizing enzyme genes on urinary nicotine metabolites levels. Methods: Uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 71 publications
(86 reference statements)
2
11
0
Order By: Relevance
“…16,18 corresponding decrease in 3HC-O-Gluc formation. 19 In the present study, deficiencies in CYP2A6 activity as measured by the NMR resulted in increased levels of nicotine-N′-oxide and decreased levels of 3HC-O-Gluc, particularly in ND subjects. The rs2431413 SNP in CYP2A6 has been associated with decreased enzyme function.…”
Section: Bergen Et Al Reported Correlations Between Urinary Nmr and Tnementioning
confidence: 46%
See 2 more Smart Citations
“…16,18 corresponding decrease in 3HC-O-Gluc formation. 19 In the present study, deficiencies in CYP2A6 activity as measured by the NMR resulted in increased levels of nicotine-N′-oxide and decreased levels of 3HC-O-Gluc, particularly in ND subjects. The rs2431413 SNP in CYP2A6 has been associated with decreased enzyme function.…”
Section: Bergen Et Al Reported Correlations Between Urinary Nmr and Tnementioning
confidence: 46%
“…In contrast, in subjects with deficient CYP2A6 activity, increased levels of nicotine‐N′‐oxide have been found 16,18 . This deficiency causes rerouting of nicotine metabolism to other pathways, including nicotine oxidation and nicotine glucuronidation, with a corresponding decrease in 3HC‐O‐Gluc formation 19 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 16 An initial screening of the inhibition potential of CBD and 7-OH-CBD against individual CYP and FMO enzymes was determined using microsomes (30–100 μg) from CYP- or FMO-overexpressing HEK293 cell lines in reactions containing either 1 or 10 μM CBD or 7-OH-CBD as potential inhibitors, nicotine or cotinine as substrates, 100 mM potassium phosphate buffer (pH 7.4), and 3 mM MgCl 2 in a final reaction volume of 30 μL. The nicotine and cotinine concentrations used in these reactions are described in Table 1 and were at or near their known Michaelis–Menten constant values ( K M ) for a given enzyme (e.g., nicotine to cotinine, 100 μM; cotinine to 3HC, 100 μM; nicotine to nornicotine, 50 μM; nicotine to NOX, 1 mM; and cotinine to COX, 1 mM 14 , 16 , 19 , 30 − 33 ). As CBD exhibits extensive nonspecific binding (70–90%) to protein and labware, low-binding 0.6 mL microcentrifuge tubes were used for all reactions.…”
Section: Methodsmentioning
confidence: 99%
“…For nicotine metabolite detection, we used a method identical to that described and validated in previous studies. 33 Briefly, nicotine, NOX, Nic-Gluc, HPBA, cotinine, COX, Cot-Gluc, 3HC, and 3HC-Gluc were detected using a UPLC (Waters Acquity; Waters Corp, Milford, MA) coupled to a triple-quadrupole mass spectrometer equipped with a Zspray electrospray ionization interface (Waters Xevo TQD; Waters Corp) by multiple reaction monitoring (MRM). While a nornicotine standard was not available for the present studies, nornicotine was identified using both parent and daughter scans to develop and confirm an MRM method for nornicotine detection.…”
Section: Methodsmentioning
confidence: 99%